Analysis of Urban Sprawl Effects on Social Vulnerability (Case Study: Qazvin City Districts) - Esfandyar Zebardast; Hossein Ghanooni (توسعه پایدار شهری)
Iran is an earthquake-prone country that many cities have experienced the earthquake. Magnitude of earthquake damage not only depends on physical destructions, but also one of the major dimensions of earthquake hazards is social vulnerability.In this research, after reviewing the theoretical literature, selected indicators for urban sprawl and social vulnerability were chosen and data were extracted from census data of Iran and Geographic Information System (GIS) for Qazvin. Then, using exploratory factor analysis with SPSS software, these indexes were used for urban sprawl overhead in four factors of density, configuration, user and access (with explanation of variance 70.22%) and in one factor for social vulnerability (with explanation of variance 66.9%) and their maps were prepared. It was clarified that among four factors of urban sprawl only density has significant relationship (0.801) with social vulnerability. The urban sprawl phenomenon also shows a weaker but still significant correlation (0.440) with social vulnerability. Regression analysis showed that urban sprawl factors can explain 67.6% of social vulnerability. The relationship between vulnerability and density/urban sprawl is positive/negative. It means that increasing social density /decreasing urban sprawl will lead to social vulnerability decreasing as well. At the end,urban sprawl and social vulnerability maps and potential development map of Qazvin city are presented based on relationship between these two phenomena.